The Role of Trichoderma, VA Mycorrhiza and Dry Yeast in the Control of Rhizoctonia Disease of Potato (Solanum tuberosum L.) (University of Khartoum Journal of Agricultural Sciences, 2025)
Laboratory and pot experiments were conducted to evaluate theefficacy of Trichoderma viride, VA mycorrhiza and dry yeast, separatelyand in combination, as an integrated strategy of Rhizoctonia diseasemanagement in potato crop. The challenge inoculation with T. viridecaused a significant reduction in vitro in the linear growth of Rhizoctoniasolani, particularly when it was performed closer to the time of pathogeninoculation. With the exception of the number of stems, yield and growthattributes of potato plants infected with R. solani were significantlyaffected. T. viride application significantly increased the growthcomponents (i.e., plant height, shoot fresh and dry weights, root fresh anddry weights) and tuber yield (i.e., number and weight of tubers) comparedto potato plants inoculated with R. solani alone. Moreover, the diseaseincidence and severity, as stem canker or black scurf on progeny tubers,were also significantly alleviated by T. viride inoculation. Similarly, VAmycorrhiza enhanced both the growth and yield measurements ofRhizoctonia-inoculated potato plants and significantly reduced theharmful effects of the disease. The dry yeast appeared to be the leastefficacious biocontrol agent to Rhizoctonia compared to the other twoorganisms; yet it also significantly improved the disease situation of theinfected plants. The combined effect of T. viride and VA mycorrhizawith or without yeast excelled other treatments in alleviation of almost alltested facets of the disease development.
Keywords: Biological control; potato stem canker; potato black scurf